REVITALISASI PENGELOLAAN ZAKAT: KONSEP YANG DIGUNAKAN MASYARAKAT DALAM MENGENTASKAN KEMISKINAN PERSPEKTIF HUKUM ISLAM - Ahmad Sainul (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aims to determine the revitalization of zakat management used by the community in alleviating poverty from an Islamic legal perspective. Uniquely, the method of collecting zakat from year to year has not developed, despite the increase in the type of community business in this modern era. Zakat is known as a potential source of funds as an effort to develop the economy of the ummah, meaning that if managed properly, it can certainly help people get out of poverty conditions so that the wealth does not only dwell on the rich. This research is included in the category of normative legal research, namely legal research that aims to examine library materials, analyzed using descriptive techniques. Aims to provide conclusions or interpretations of law that are objective. The findings of this study show that one of the lessons of zakat is to improve the economy of the ummah in alleviating poverty. Not only that, the existence of zakat can have a positive influence on economic improvement in the community. This can happen, if zakat management is done well. As in the form of productive zakat, zakat funds should be given for the development of small businesses such as clone traders, cake sellers, chicken livestock, fish livestock and fried food sellers. One of the goals is that the community gets the benefits directly, so that in the use of zakat funds can be constructed, which initially as mustahik turned into muzakki.